Simultaneous detection of decidual Th1/Th2 and NK1/NK2 immunophenotyping in unknown recurrent miscarriage using 8-color flow cytometry with FSC/Vt extended strategy. Issue 3 (19th May 2017) - Dong, Peng; Wen, Xi; Liu, Jia; Yan, Cui-Yan; Yuan, Jing; Luo, Lan-Rong; Hu, Qiao-Fei; Li, Jian
Abstract : Th1/Th2 imbalance is considered as a mechanism for recurrent miscarriage. The NK1/NK2 paradigm is hypothesised to play an important role in pregnancy. However, few results showed simultaneous changes of these subsets in vivo in decidual tissues. The present study aimed to detect the decidual mononuclear cells (dMo), and the Th1/Th2, and NK1/NK2 paradigm simultaneously using multiparametric flow cytometry (MFC) in unexplained recurrent miscarriages (URM). Mononuclear cells were isolated from the decidual tissues of URM cases and early pregnant women. The mononuclear cell percent was demonstrated by detecting the expression of CD3, CD4, CD8, CD56, and CD16 extracellular markers, interferon (IFN)-γ, and interleukin (IL)-4 intracellular markers in live cells using 8-color flow cytometry with forward scatter (FSC)/side scatter (SSC) and FSC/viability (Vt) initial gating strategies, and the ratios of Th1/Th2 and decidual NK1 (dNK1)/decidual NK2 (dNK2) cells were compared between the subject groups. Two initial gating strategies of the FSC/SSC or FSC/Vt, with central or extended gating scales, were adapted, and there was no main effect or interaction for the cell proportions, except for the type 1 and type 2 subsets in the FSC/Vt extended gating strategy. There was no significant difference of the proportions of the decidual T, dNK, NKT-like, Th, and Tc cells between the two groups. However, the Th1/Th2 and dNK1/dNK2 ratios in the URM patients were higher compared with the normal group when using the FSC/Vt extended gating strategy. The present study provides means to detect Th1/Th2 and dNK1/dNK2 simultaneously in URM patients for large sample investigations in the future.